2014
DOI: 10.1016/j.measurement.2013.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Real time control of the ASBGo walker through a physical human–robot interface

Abstract: In this work it is presented the development of the conceptual design, implementation and validation of a Smart walker with an inexpensive integrated interface. This interface is based on a joystick and it intends to extract the user's command intentions. Preliminary sets of experiments were performed which showed the sensibility of the joystick to extract navigation commands from the user. These signals presented a higher frequency component that was attenuated by a Benedict-Bordner g-h filter. The resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Many controllers have been proposed, based on various measurable parameters. For example, JARoW continuously matches its center to the center of its user's legs while ASBGo translates force in its handles to velocity (Lee et al, 2014;Martins et al, 2014). However, it is not known how well these SW prototypes achieve the four aspects discussed herein.…”
Section: Discussionmentioning
confidence: 99%
“…Many controllers have been proposed, based on various measurable parameters. For example, JARoW continuously matches its center to the center of its user's legs while ASBGo translates force in its handles to velocity (Lee et al, 2014;Martins et al, 2014). However, it is not known how well these SW prototypes achieve the four aspects discussed herein.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, because a walker does not require much coordinated movement of the upper limbs, technology-based walkers are being developed. Recently, a smart walker for mobility assistance and monitoring system aid, ASBGo, was developed and reported to improve gait parameters and postural stability in patients with SCA [114,115]. In addition to technology, some studies on walking assistance using dogs and handkerchiefs have also been reported.…”
Section: Assistive Technologymentioning
confidence: 99%
“…This is a mechanical design based on the imitation of the caregivers' motion during the support task, which is mainly composed of back support, a robot arm and an active walker. Bauzel et al [4,5] analyzed current research on smart walkers and proposed three required significant features: provide dynamic support, demand little or no effort to use, be user-friendly. Also, a new user interface which allows users to control the walker intuitively was designed and implemented on a ASBGO walker, which is an active robotic walker that assists the elderly and disabled people in walking.…”
Section: A Literature Reviewmentioning
confidence: 99%